2022
DOI: 10.3389/fcvm.2022.863642
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Machine Learning Techniques for Prediction of Intensive Care Unit Length of Stay in Heart Transplantation Patients

Abstract: BackgroundPost-operative heart transplantation patients often require admission to an intensive care unit (ICU). Early prediction of the ICU length of stay (ICU-LOS) of these patients is of great significance and can guide treatment while reducing the mortality rate among patients. However, conventional linear models have tended to perform worse than non-linear models.Materials and MethodsWe collected the clinical data of 365 patients from Wuhan Union Hospital who underwent heart transplantation surgery betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Yan et al found that DeepSurv was the most successful model in predicting the prognosis of chondrosarcoma compared with the RSF, CoxPH, and NMTLR models 11 . Deep learning can convert linear and nonlinear predictor variables into linear combinations to predict the prognosis of patients by using multistage neural networks and reduce the structural bias associated with missing follow‐up information, which can predict the survival probability of patients at any time point 27,29 . Therefore, when dealing with large samples and multivariate and nonlinear data, the DeepSurv model has obvious advantages in prediction compared with other models.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al found that DeepSurv was the most successful model in predicting the prognosis of chondrosarcoma compared with the RSF, CoxPH, and NMTLR models 11 . Deep learning can convert linear and nonlinear predictor variables into linear combinations to predict the prognosis of patients by using multistage neural networks and reduce the structural bias associated with missing follow‐up information, which can predict the survival probability of patients at any time point 27,29 . Therefore, when dealing with large samples and multivariate and nonlinear data, the DeepSurv model has obvious advantages in prediction compared with other models.…”
Section: Discussionmentioning
confidence: 99%
“…Only 15 manuscripts described model interpretability. Additive exPlanations (SHAP), which quantifies the contribution of each feature (variable) to the predicted outcome related to a specific instance (12,13). The rest of the papers used feature importance to explain the outcome of their ML models.…”
Section: Summary Of Ai Methodsmentioning
confidence: 99%
“…This could introduce systematic difference between training, testing, and validation datasets, thus confounding algorithm development (11). Algorithms applied to local datasets showed much higher performance upon validation, likely due to better data homogeneity (12,13).…”
Section: Post Heart Transplant Outcome Predictionmentioning
confidence: 99%
See 1 more Smart Citation